2017
DOI: 10.1137/16m1060741
|View full text |Cite
|
Sign up to set email alerts
|

Inducibility in Binary Trees and Crossings in Random Tanglegrams

Abstract: Abstract. In analogy to other concepts of a similar nature, we define the inducibility of a rooted binary tree. Given a fixed rooted binary tree B with k leaves, we let γ(B, T ) be the proportion of all subsets of k leaves in T that induce a tree isomorphic to B. The inducibility of B is lim sup |T |→∞ γ(B, T ). We determine the inducibility in some special cases, show that every binary tree has positive inducibility and prove that caterpillars are the only binary trees with inducibility 1. We also formulate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 22 publications
2
33
0
Order By: Relevance
“…To this day, there is substantial activity regarding this concept. In analogy to (Pippenger and Golumbic, 1975), the inducibility of a rooted tree S with k leaves is defined as the maximum frequency at which S can appear as a subtree induced by k leaves of an arbitrary rooted tree whose number of leaves tends to infinity (Czabarka et al, 2017(Czabarka et al, , 2020Dossou-Olory and Wagner, 2019). Bubeck and Linial (2016) defined the inducibility of a tree S with k vertices as the maximum proportion of S as a subtree among all k-vertex subtrees of a tree whose number of vertices tends to infinity.…”
Section: Introduction and Previous Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this day, there is substantial activity regarding this concept. In analogy to (Pippenger and Golumbic, 1975), the inducibility of a rooted tree S with k leaves is defined as the maximum frequency at which S can appear as a subtree induced by k leaves of an arbitrary rooted tree whose number of leaves tends to infinity (Czabarka et al, 2017(Czabarka et al, , 2020Dossou-Olory and Wagner, 2019). Bubeck and Linial (2016) defined the inducibility of a tree S with k vertices as the maximum proportion of S as a subtree among all k-vertex subtrees of a tree whose number of vertices tends to infinity.…”
Section: Introduction and Previous Resultsmentioning
confidence: 99%
“…The concept of inducibility of a tree with k leaves is still new and the precise value of the inducibility is known only for a few classes of trees, most of them exhibiting a symmetrical configuration. The recent paper (Czabarka et al, 2017) raised some questions on the inducibility of binary trees, one of which is discussed and approximately solved within this note. The present paper also covers a related problem concerning the inducibility of a ternary tree with four leaves.…”
Section: Introduction and Previous Resultsmentioning
confidence: 99%
“…Note that the (graph) crossing number cr( ) of a tanglegram is less or equal to the (tanglegram) crossing number crt( ) of , since the tanglegram layout is more restrictive than the graph drawing. The following proposition that provides an almost obvious characterization of planarity of tanglegram, was found by [25] and later rediscovered [8]:…”
Section: Tanglegram Crossing Number and Planarit Y Of Tanglegramsmentioning
confidence: 98%
“…Otherwise it is called nonplanar . In an earlier article , we showed that the tanglegram crossing number of a randomly and uniformly selected tanglegram of size n is Θ(n2) with high probability, i.e. as large as it can be within a constant multiplicative factor.…”
Section: Tanglegram Crossing Number and Planarity Of Tanglegramsmentioning
confidence: 99%
See 1 more Smart Citation